Businesses' contributions to sustainable development goal 5 : gender equality across B Corps in Latin America and the Caribbean - Paludi, Mariana Inés; Funes, María Eugenia; Krysa, Isabella; Pérez, Rodrigo; Cazzuffi, Chiara (Emerald Publishing Limited, 2023)
Since 2015, businesses have been identified as key actors in the achievement of the United Nations Sustainable Development Goals. Analyzing the impact of B-certification in terms of gender equality among Latin American and Caribbean companies, Businesses' Contributions to Sustainable Development Goal 5 champions the potential B-certification has for the advancement of gender equality in the private sector. Including a historical account of the B Corps movement, the authors assess the capacity of different tools to measure businesses' contributions to gender equality and analyze gender equality performance across Latin American and Caribbean companies. Featuring a review of related literature, chapters also consider how women's movements and gender struggles have attracted new activists which have increased their visibility in the region's public arenas. Highlighting the connection between business, sustainability and gender and providing inspiration for the wider business world, this book identifies best practices for the achievement of gender equality from B Corps across South America.
Keywords: Sex discrimination in employment -- Latin America.; Sex discrimination in employment -- Caribbean Area.; Diversity in the workplace -- Latin America.; Diversity in the workplace -- Caribbean Area.; Sustainable development -- Latin America.; Sustainable development -- Caribbean Area.; Business & Economics, Workplace Harassment & Discrimination.; Office & workplace.; elektronické knihy; electronic books